Biophysical regulation of local chromatin structure. (April 2019) - Gilbert, Nick
Abstract : DNA in higher eukaryotes is packaged with histone proteins to form nucleosomes which are further assembled into higher-order chromatin fibres to protect and regulate access to the genetic information. Chromatin folding above the nucleosomal level is controversial with differing views proposing unfolded irregular structures through to highly organised chromatin fibres. Using a combination of techniques including sedimentation studies, electron microscopy and superresolution imaging views are converging to indicate that local chromatin is organised into a fibre, peppered with numerous discontinuities and points of flexibility. Reconciliation of different views suggests that in vitro and in vivo data are generally consistent but questions remain on how chromatin packaging is altered by cellular processes such as transcription, enzymatic chromatin remodelling and elusive DNA supercoiling.